Can Routine Blood and Urine Parameters Reveal Clues to Detect Bladder Cancer? A Case–Control Study - Wang, Dan-Qi; Shuai, Juan; Zheng, Hang; Guo, Zhong-Qiang; Huang, Qiao; Xu, Xiao-Feng; Li, Xiao-Dong; Zi, Hao; Ming, Dao-Jing; Ren, Xuan-Yi; Zeng, Xian-Tao (Frontiers in Oncology, 2022)
Objective: Limited attention has been paid to abnormal blood and urine tests results for patients with bladder cancer. The present study aimed to identify whether blood and urine parameters are associated with bladder cancer. Methods: We used a case-control design and matched each patient with bladder cancer with three healthy controls for age and sex. Univariate conditional logistic regression was used to calculate the crude and adjusted odds ratio (OR) and its 95% confidence interval (CI). Multivariate conditional logistic regression was performed for confounders adjustment, and Spearman’s correlation coefficient was used to assess the correlation between tumor T stages and urine parameters. Results: Patients with bladder cancer (n = 360) and controls (n =1050) were recruited. In the univariate conditional logistic analysis, higher urine pH was associated with a decreased risk of bladder cancer (OR = 0.67, 95% CI = 0.57–0.78); while higher values of urine protein (OR = 4.55, 95% CI = 3.36–6.15), urine glucose (OR = 1.56, 95% CI = 1.18–2.05), and urine occult blood (OR = 4.27, 95% CI = 3.44–5.29) were associated with an increased risk of bladder cancer. After adjustment for body mass index, fasting blood glucose, hypertension, red blood cells, white blood cells, lymphocytes, neutrophils, and platelets, significance still remained for urine pH (OR = 0.68, 95% CI = 0.53–0.88), urine protein (OR = 1.97, 95% CI = 1.21–3.19), urine glucose (OR = 2.61, 95% CI = 1.39–4.89), and urine occult blood (OR = 3.54, 95% CI =2.73–4.58). Conclusion: This study indicated that lower urine pH, a higher value of urine protein, urine glucose, and urine occult blood might be risk factors for bladder cancer.